Cause and Effect in Political Polarization: A Dynamic Analysis - Callander, Steven; Carbajal, Juan Carlos (Journal of Political Economy, 2022)
Polarization is both a description of the current state of politics and a dynamic path that has rippled across the political domain over decades. We provide a simple model that explains why polarization appears incrementally and why it was elites who polarized first and more dramatically, whereas mass polarization came later and has been less pronounced. We incorporate an ostensibly unrelated finding about how voters form preferences into a dynamic model of elections. This change, when combined with the response of strategic candidates, creates a feedback loop that can replicate many features of the data. We explore the model’s implications for other aspects of politics and trace what it predicts for the future of polarization.